Violation of Gandhian Philosophy of Education and its Socioeconomic Consequences - Prabhu, Devidas S. (Prabandhan: Indian Journal of Management, 2013)
Learning in the mother tongue is the best and the easiest way of acquiring knowledge, which has been followed by almost all the developed countries of the world. Mahatma Gandhi strongly advocated mother tongue based education in India; he considered English as the greatest evil among all the evils of foreign rule. The education system based on English has been continued even after independence, which has remained a constraint for the masses. There are many adverse effects of violation of the Gandhian philosophy of education. Exploitation of the rural people, increased dependency on agriculture, mass poverty, backwardness in science and technology, wastage of human resources, exclusive growth, growing economic inequality, lack of original thought and independent policies, promotion of inefficient people, growing unemployment, decline in patriotism leading to corruption and inefficiency, brain drain, and slow economic development are the consequences of an English education system. India cannot be compared with small countries; some states are bigger than many European countries. Hence, it is unscientific to think that every Indian should learn in one language - that is English. All kinds of education should be developed in major Indian languages so as to educate the masses.